Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

Impact of Fly Ash on the CO2 Mineralization Efficiency and Interfacial Transition Zone Properties of Sustainable Coal Gangue-based Materials - Lei Qin; Feilong Zhang; Zitong Xue; Hui Wang; Miao Mu; Meiling Xiong; Niandong Chen (Water, Air, & Soil Pollution, 2026)

Study on the removal effect of Enteromorpha polysaccharide on heavy metal-organic composite pollution - Xue Shen; Yingqiang Li; Meiling Li; Yaru Zai; Xue Han; Shida Zhang; Jin Wang; Zhigang Yang; Yang Song (Journal of Environmental Chemical Engineering, 2026)

Co-exposure to PS-NPs and HFPO-TA potentiates reproductive toxicity via ferroptosis and SLC1A5-Mediated glutamine deprivation in male mice - Lihai Wu; Jing Ding; Jiayu Xue; Meiling Le; Yiqi Wan; Wanting Zhao; Yangyang Yuan; Xiaodong Kuang; Xinyuan zhao; Liping Zheng; Dalei Zhang (Chemico-Biological Interactions, 2026)

Construction of a plasmid-based reverse genetics system for the rescue of shrimp infectious covert mortality nodavirus (CMNV) and use in deciphering the role of its B2 protein in regulating its cross-species infectivity - Zhenxin Zhao; Ting Xue; Jinwu Wang; Rui Xiao; Yue Zhang; Meiling Sun; Qingli Zhang; Huarong Guo (Aquaculture, 2026)

Singlet oxygen-dominated dual-pathways catalytic ozonation of sulfamethoxazole over FeOx-N-BC/O3–MNBs system - Meiling Cai; Xiaojun Miao; Xiaoyan Wang; Xueyan Xue; Hui Zhu; Liping Yang; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2026)

Pore Structure Characteristics and Controlling Factors of Different Lithofacies in Lacustrine Shale: A Case Study of Fengcheng Formation in Mahu Sag, Junggar Basin - Jiahao Lyu; Fujie Jiang; Jing Xue; Tao Hu; Yuping Wu; Chenxi Zhang; Meiling Hu; Renda Huang (Journal of Earth Science, 2026)

Bio-inspired fabrication of heterostructured porous core-shell PANI@Cu2O/CMC composite beads for green catalysis in A3 and decarboxylative A3 couplings - Shuyao Zhang; Ting Lin; Yuling Huang; Jiayi Huang; Meiling Xue; Zhihao Shan; Yiqun Li (Sustainable Chemistry and Pharmacy, 2025)

EDIL3 induced by GLIS2 suppresses the anti-tumor activity of CD8+ T cells and expedites epithelial-mesenchymal transition in thyroid cancer - Xu Qian; Bo Fu; Shuangfu Peng; Meiling Xue; Zhaohui Zhu; Dan Yao (Journal of Molecular Histology, 2025)

Hypoxia exacerbate the marine ecological risk of arsenic: By stimulating its migration and release at the sediment-water interface - Liqin Duan; Jinming Song; Meiling Yin; Xiaoqi Liu; Xue Liu; Xuegang Li; Huamao Yuan (Water Research, 2025)

Genome Mining Analysis Uncovers the Previously Unknown Biosynthetic Capacity for Secondary Metabolites in Verrucomicrobia - Xue Di; Peng Li; Jingxuan Wang; Vincent Nowak; Shuai Zhi; Meiling Jin; Liwei Liu; Shan He (Marine Biotechnology, 2024)

m6A-mediated HDAC9 upregulation promotes particulate matter-induced airway inflammation via epigenetic control of DUSP9-MAPK axis and acts as an inhaled nanotherapeutic target - Yingying Zeng; Xin Bai; Guiping Zhu; Mengchan Zhu; Wenjun Peng; Juan Song; Hui Cai; Ling Ye; Cuicui Chen; Yuanlin Song; Meiling Jin; Xue-Qing Zhang; et al. (Journal of Hazardous Materials, 2024)

Microbial role in enhancing transfer of straw-derived nitrogen to wheat under nitrogen fertilization - Shuyu Huang; Xue Gao; Li Zeng; Meiling Zhang; Liyu Zhang; Shiyu Wang; Yuanzheng Zhao; Wei Zhou; Chao Ai (Soil and Tillage Research, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Evaluation of magnetic calcium silicate hydrate derived from halloysite clay for efficient phosphate capture - Debin Jiang; Xue Long; Meiling Xiang; Xiantian Gan; Qinghong Pu; Yu Chen; Ning Qi; Xiaoping Wang (Journal of Environmental Chemical Engineering, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Exposure to ambient air pollutants is associated with an increased incidence of hyperuricemia: A longitudinal cohort study among Chinese government employees - Lidan Duan; Muyang Zhang; Yuhan Cao; Yuwei Du; Meiling Chen; Rumeng Xue; Minxue Shen; Dan Luo; Shuiyuan Xiao; Yanying Duan (Environmental Research, 2023)

Characterisation of kapok fibre's biochar for arsenate adsorption removal from aqueous solution. - Kanfolo Franck Herve Yeo; Yingying Dong; Tongxuan Xue; Zhiwen Chen; Nan Zhang; Ye Yang; Liu Han; Meiling Liu; Ange Nsilani Kouediatouka; Hanse Pablick Patherny Lobo Mouguegue; Wendong Wang (Environmental Research, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

Long-term effect of submicronic particulate matter (PM1) and intermodal particulate matter (PM1-2.5) on incident dyslipidemia in China: A nationwide 5-year cohort study - Meiling Hu; Jing Wei; Yaoyu Hu; Xiuhua Guo; Zhiwei Li; Yuhong Liu; Shuting Li; Yongxi Xue; Yuan Li; Mengmeng Liu; Lei Wang; Xiangtong Liu (Environmental Research, 2023)

Morphological and endogenous phytohormone changes during long-term embryogenic cultures in Korean pine - Yan Liang; Xin Xu; Hailong Shen; Meiling Gao; Yan Zhao; Xue Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Mechanism of interactions between α-conotoxin RegIIA and carbohydrates at the human α3β4 nicotinic acetylcholine receptor - Meiling Zheng; Han-Shen Tae; Liang Xue; Tao Jiang; Rilei Yu (Marine Life Science & Technology, 2022)
Conotoxins are marine peptide toxins from marine cone snails. The α-conotoxin RegIIA can selectively act on human (h) α3β4 nicotinic acetylcholine receptor (nAChR), and is an important lead for drug development. The high-resolution cryo-electron microscopy structure of the α3β4 nAChR demonstrates several carbohydrates are located near the orthosteric binding sites, which may affect α-conotoxin binding. Oligosaccharide chains can modify the physical and chemical properties of proteins by changing the conformation, hydrophobicity, quality and size of the protein. The purpose of this study is to explore the effect of oligosaccharide chains on the binding modes and activities of RegIIA and its derivatives at hα3β4 nAChRs. Through computational simulations, we designed and synthesized RegIIA mutants at position 14 to explore the importance of residue H14 to the activity of the peptide. Molecular dynamics simulations suggest that the oligosaccharide chains affect the binding of RegIIA at the hα3β4 nAChR through direct interactions with H14 and by affecting the C-loop conformation of the binding sites. Electrophysiology studies on H14 analogues suggest that in addition to forming direct interactions with the carbohydrates, the residue might play an important role in maintaining the conformation of the peptide. Overall, this study further clarifies the structure–activity relationship of α-conotoxin RegIIA at the hα3β4 nAChR and, also provides important experimental and theoretical basis for the development of new peptide drugs.

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

Proteomic Analysis of Serum Differentially Expressed Proteins Between Allergic Bronchopulmonary Aspergillosis and Asthma - Hui Cai; Diquan Shuai; Xiaomin Xue; Yuqing Mo; Xixi Song; Ling Ye; Shuiming Li; Daiwei Wang; Yun Wang; Meiling Jin (Mycopathologia, 2021)

Sialoglycoproteins Isolated from the Eggs of Gadus morhua Inhibit Bone Resorption in Ovariectomized Rats by Suppressing the MAPK and NF-κB Pathways - Lei Mao; Yiming Wang; Meiling Wang; Yufeng Dai; Jingfeng Wang; Changhu Xue (Journal of Ocean University of China, 2019)

Sialoglycoprotein isolated from Carassius auratus eggs promotes osteogenesis by stimulating mesenchymal stem cells to commit to osteoblast differentiation - Lei Mao; Meiling Wang; Xingjun Xi; Yufeng Dai; Na Wang; Jingfeng Wang; Changhu Xue (Cell and Tissue Research, 2019)

Periodic Variation of AAK1 in an Aβ1–42-Induced Mouse Model of Alzheimer’s Disease - Xue Fu; Meiling Ke; Weihua Yu; Xia Wang; Qian Xiao; Min Gu; Yang Lü (Journal of Molecular Neuroscience, 2018)

Resveratrol protects against arsenic trioxide-induced nephrotoxicity by facilitating arsenic metabolism and decreasing oxidative stress - Meiling Yu; Jiangdong Xue; Yijing Li; Weiqian Zhang; Dexing Ma; Lian Liu; Zhigang Zhang (Archives of Toxicology, 2013)

Structure and seasonal dynamics of bacterial communities in three urban rivers in China - Meiling Zhang; Na Yu; Liqiao Chen; Caihong Jiang; Yanjie Tao; Tian Zhang; Jun Chen; Di Xue (Aquatic Sciences, 2012)

Molecular characterization of the bacterial composition in two waste silk refining systems - Meiling Zhang; Xuexia Yang; Tian Zhang; Jun Chen; Di Xue (World Journal of Microbiology and Biotechnology, 2011)